Assessment of the imaging quality and heterogeneous predictive value of readout-segmented echo planar imaging for diffusion-weighted rectal MRI - Song, Mingrui; Liang, Yichuan; Wang, Huiying; Shi, Lei; Mao, Quanliang; Zhao, Haonan; Zhang, Zhehao; Li, Aijing; Pan, Yuning (Frontiers in Oncology, 2025)
ObjectivesTo qualitatively and quantitatively compare the image quality of readout-segmented echo planar imaging (rs-EPI) and single-shot echo planar imaging (ss-EPI) for diffusion-weighted (DWI) rectal MRI, as well as the heterogeneous predictive value of the apparent diffusion coefficient (ADC) values obtained by the two DWI techniques.MethodsThe rs-EPI and ss-EPI images were subjectively assessed for lesion sharpness, display of normal structure, overall image quality, geometric distortion, and anatomical differences. The signal-to-noise ratio (SNR), contrast ratio (CR), contrast-to-noise ratio (CNR), and ADC values were objectively compared. Pearson’s correlations and ROC analysis were used to explore the relationships of ADC values obtained by the two techniques and nucleus related antigen (Ki-67) and hypoxia inducible factor-1α (HIF-1α).ResultsEighty patients with rectal cancer (RC) were included. Lesion sharpness, normal structure display, overall image quality, geometric distortion and anatomical structure differences in the rs-EPI DWI group were higher than in the ss-EPI DWI group (P<0.001). SNR, CNR and CR in the rs-EPI DWI group were higher than in the ss-EPI DWI group (P<0.001). ADC values were not different. ROC analysis showed that the area under the curve (AUC) of high Ki-67 and HIF-1α expression levels as predicted by the average ADC of ss-EPI and rs-EPI DWI were 0.82 (95%CI: 0.72-0.92), 0.77 (95%CI: 0.67-0.88), and 0.81 (95%CI: 0.72-0.91), 0.82 (95%CI: 0.72-0.91), respectively, with similar predictive values between the 2 techniques (P=0.23, 0.75).Conclusionrs-EPI DWI can improve image quality and the ADC value is associated with pathologic markers of tumor aggression.